Emotional State During Tasting Affects Emotional Experience Differently and Robustly for Novel and Familiar Foods - Kaneko, Daisuke; Brouwer, Anne-Marie; Hogervorst, Maarten; Toet, Alexander; Kallen, Victor; van Erp, Jan B. F. (Frontiers in Psychology, 2020)
Emotional state during food consumption is expected to affect food pleasantness. We hypothesize that a negative emotional state reduces food pleasantness, and more so for novel foods than for familiar foods because novel foods have not yet been associated with previous emotions. Furthermore, we expect this effect to be stronger when judging the food again from memory without tasting. We induced a positive emotional state in 34 participants by telling them that they earned a monetary bonus, and induced a negative emotional state in 35 other participants by subjecting them to a social stress test. After this emotion induction, both groups tasted and rated a (for them) novel soup (sumashi soup) and a familiar soup (vegetable soup). Several explicit and implicit measures of food pleasantness (rated valence, EsSense25, willingness-to-take-home and sip size) indicated that while the negative emotion group did not experience the soups as less pleasant than the positive emotion group, there was an interaction between food familiarity and emotional group. The positive emotion group experienced novel and familiar soups about equally pleasant, while the negative emotion group experienced the novel soup as relatively unpleasant and the familiar soup as pleasant. The latter result is consistent with a comforting effect of a familiar taste in a stressful situation. This effect remained in the ratings given one week later based on memory, and even after re-tasting. Our results show that emotional state affects food pleasantness differently for novel and familiar foods and that such an effect can be robust.